Effect of Air-fuel Ratio on the Combustion Characteristics of Syngas (H2:CO) in Direct-injection Spark-ignition Engine - Hogas, F. Y.; A. Rashid, A. Aziz; Shaharin, A. Sulaiman (Elsevier Ltd, 2014)
This paper presents experimental results of the effect of air-fuel ratio on the combustion characteristics of a directinjection spark-ignition engine fuelled with a syngas of H2/CO composition of equal molar ratio. The engine was operated at fully open throttle and the start of fuel injection (SOI) was set at 180o before top dead center (BTDC). The spark advance was set to the minimum advance for a maximum brake torque. The experiment was conducted at lean mixture conditions with engine speed ranging from 1500 to 2400 rev/min. The results show that syngas operated under wider operation excess air ratio (λ) as compared to CNG at the same engine speed. The minimum ignition advance for maximum brake torque and combustion duration were observed to increase with an increase in λ. The effect of air-fuel ratio was more visible on the initial stage of the combustion at lower speeds while it is visible on the rapid burning stage at higher speeds. Moreover, the combustion duration was increased with an increase in engine speed.